(untitled) (Bangladesh Pharmaceutical Journal, 2019)
Boehmeria glomerulifera Miq., is medicinal herb belongs to the family Urticaceae. It is used for treating various diseases by folk practitioners and rural people. The CNS antidepressant and antidiarrhoeal activities of the crude extract were investigated at 200 and 400 mg/kg bw in Swiss Albino mice model. The crude methanolic extract revealed significant (p < 0.05) antidepressant activity in mice at 400 mg/kg bw. On the other hand, in the castor oil-induced antidiarrheal assay, the extract demonstrated significant (p < 0.05) antidiarrhoeal activity at 400 mg/kg bw. Bangladesh Pharmaceutical Journal 22(2): 181-184, 2019